Material sensitivity of patient-specific finite element models in the brace treatment of scoliosis - Wenqing Wei; Tianyuan Zhang; Junlin Yang; Junlin Yang; Yu Qian; Yating Dong (Frontiers in Bioengineering and Biotechnology, 2023)
Objectives: To study the mechanical sensitivity of different intervertebral disc and bone material parameters and ligaments under different force configurations and magnitudes in the scoliosis model.Methods: The finite element model of a 21-year-old female is built using computed tomography. Local range of motion testing and global bending simulations are performed for the model verification. Subsequently, Five force of different directions and configurations were applied to the finite element model applying the brace pad position. The material parameters of the model were related to different spinal flexibilities and included different material parameters of cortical bone, cancellous bone, nucleus and annulus. The virtual X-ray technique measured Cobb angle, thoracic Lordosis, and lumbar Kyphosis.Results: The difference in peak displacement is 9.28 mm, 19.99 mm, 27.06 mm, 43.99 mm, and 50.1 mm under five force configurations. The maximum Cobb angle difference due to material parameters are 4.7° and 6.2°, which are converted to thoracic and lumbar in-brace correction difference of 18% and 15.5%. The maximum difference in Kyphosis and Lordosis angle is 4.4° and 5.8°. The average thoracic and lumbar Cobb angle variation difference in intervertebral disc control group is larger than that in bone control group, while the average Kyphosis and Lordosis angle is inverse. The displacement distribution of models with or without ligaments is similar, with a peak displacement difference of 1.3 mm in C5. The peak stress occurred at the junction of the cortical bone and ribs.Conclusion: Spinal flexibility largely influences the treatment effect of the brace. The intervertebral disc has a greater effect on the Cobb angle, the bone has a greater effect on the Kyphosis and Lordosis angles, and the rotation is affected by both. Patient-specific material is the key to increasing accuracy in the personalized finite element model. This study provides a scientific basis for using controllable brace treatment for scoliosis.